Evaluation of Postoperative Clinical and Functional Results in Morbidly Obese Individuals Undergoing Primary Total Knee Replacement: A Cross-Sectional Study - Zahir Khan, Rumman, Ashraf, Muhammad Luqman, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Total knee arthroplasty (TKA) is a well-established procedure for treating end-stage knee osteoarthritis (OA), offering significant pain relief and improving the quality of life. However, morbid obesity greater than 40 kg/m², presents unique challenges in surgical outcomes, with potential complications affecting both the procedure and recovery. Methods: A cross-sectional study was conducted at the Department of Orthopedics, MMC Mardan, from January 2018 to December 2022, involving 236 morbidly obese patients scheduled for primary unilateral. Demographic data, comorbidities, and surgical details were extracted from medical records. Statistical analysis included paired t-tests to compare preoperative and postoperative scores, with significance set at p < 0.05. Results: The mean age of the patients was 59.23 ± 5.66 years. A majority (90.3%) underwent bilateral TKA, with the rest having unilateral procedures. BMI distribution showed 58.9% of patients had a BMI between 38-48 kg/m², 28% had a BMI between 49-50 kg/m², and 13.1% had a BMI greater than 50 kg/m². At the one-year follow-up, significant improvements were observed in pain (p = 0.031), joint stability (p = 0.022), and ROM (p = 0.021). However, no significant improvements were found in functional outcomes, including walking distance (p = 0.037), stair climbing (p = 0.029), and stair descending (p = 0.001). Conclusion: TKA provides significant clinical benefits, particularly in pain relief, joint stability, and ROM, in morbidly obese patients. However, the lack of substantial functional improvements postoperatively highlights the need for further research on optimizing rehabilitation strategies. Keywords: Total knee arthroplasty, morbid obesity, clinical outcomes, functional outcomes, American Knee Society Score.